First case of intravenous drug use-related candidemia in Türkiye - Kaya, Abdurrahman; Zerdali, Hasan; Koç, Buse; Tozalgan, Ümit; Çiftçi, Can; Mert, Ali (My University, 2024)
Although Candida species are normal flora elements of the body, they can cause various diseases from mucocutaneous infections to candidemia. The presence of a central venous catheter, use of broad-spectrum antibiotics, parenteral nutrition, dialysis, neutropenia, malignancy, and immunosuppressive treatments are the most reported risk factors for candidemia. Complications that develop during follow-up increase both morbidity and mortality. The incidence of fungal infections has been increasing in recent years. This increase is also seen in intravenous drug users. In these patients, candidemia can cause serious life-threatening complications including septicemia and end-organ failure. To date, no cases of intravenous drug use-related candidemia have been reported in our country. This patient represents the first documented case. In this case, we aim to draw attention to the relationship between intravenous drug use and candidemia.

Kandida türleri, vücudun normal flora elemanları olmalarına rağmen mukokutanöz infeksiyonlardan kandidemiye kadar birçok değişken hastalığa neden olabilmektedir. Santral venöz kateter varlığı, geniş spektrumlu antibiyotik kullanımı, parenteral beslenme, diyaliz, nötropeni, malignite ve immünsupresif tedaviler kandidemi için en çok bildirilen risk faktörleridir. Kandidemi sırasında gelişen komplikasyonlar ise hem morbiditeyi hem de mortaliteyi arttırmaktadır. Mantar infeksiyonlarının insidansı son yıllarda artış göstermektedir. Bu artıştan intravenöz ilaç bağımlısı olan bireylerde nasibini almaktadır. Bu hastalarda kandidemi, sepsis ve organ yetmezliği gibi hayatı tehdit eden ciddi komplikasyona neden olabilmektedir. Şu ana kadar ülkemizden bildirilmiş intravenöz ilaç kullanımına bağlı kandidemi olgusu yoktur. Bu yönüyle bu hasta ilk vaka olma özelliği göstermektedir. Bu vakada amacımız, intravenöz ilaç kullanımı ile kandidemi arasındaki ilişkiye dikkat çekmektir.
Türkiye’de intravenöz ilaç kullanımına bağlı ilk kandidemi vakası
Keywords: Candidemia; Intravenous Drug Use; Hemoculture; Kandidemi; Damar İçi İlaç Kullanımı; Kan Kültürü